set adds = the addF of V | [:(a * V),(a * V):];
[:(a * V),(a * V):] c= [: the carrier of V, the carrier of V:] by ZFMISC_1:96;
then [:(a * V),(a * V):] c= dom the addF of V by FUNCT_2:def 1;
then A1: dom ( the addF of V | [:(a * V),(a * V):]) = [:(a * V),(a * V):] by RELAT_1:62;
for z being object st z in [:(a * V),(a * V):] holds
( the addF of V | [:(a * V),(a * V):]) . z in a * V
proof
let z be object ; :: thesis: ( z in [:(a * V),(a * V):] implies ( the addF of V | [:(a * V),(a * V):]) . z in a * V )
assume A2: z in [:(a * V),(a * V):] ; :: thesis: ( the addF of V | [:(a * V),(a * V):]) . z in a * V
consider x, y being object such that
A3: ( x in a * V & y in a * V & z = [x,y] ) by ;
consider v being Element of V such that
A4: x = a * v by A3;
consider w being Element of V such that
A5: y = a * w by A3;
( the addF of V | [:(a * V),(a * V):]) . z = (a * v) + (a * w) by
.= a * (v + w) by VECTSP_1:def 14 ;
hence ( the addF of V | [:(a * V),(a * V):]) . z in a * V ; :: thesis: verum
end;
hence the addF of V | [:(a * V),(a * V):] is Function of [:(a * V),(a * V):],(a * V) by ; :: thesis: verum